Effect of Spacing on Biomass Production, Nutrient Content and Uptake by Poplar (Populus deltoides) Plantations - Kumar, Satish; Kumar, Ravi; Kumar, Neeraj; Singh, Rajendra (Indian Forester, 2011)
A study was conducted to estimate the biomass production and nutrient removal by eight years old poplar plantation raised at different spacing in a replicated randomized block design having three spacing of 5 × 4 m, 10 × 2.5 m and 15 × 2.5 m. Biomass of all the plant parts decreased with increasing tree spacing except that the differences between 10 × 2.5 m and 15 × 2.5 m spacing in respect of leaves and branches biomass were not significant. The total tree biomass including litter fall was higher in 5 × 4 m (415 t/ha) followed by 10 × 2.5 m (330 t/ha) and 15 × 2.5 m (192 t/ha) spacing. Concentration of both primary and secondary nutrients in different plant parts differed significantly at different spacing. Maximum nutrient concentration was recorded in leaves at 15 × 2.5 m spacing. However, poplar stem accounted for maximum uptake of all the nutrients. Among poplar spacing, closer tree spacing of 5 × 4 m recorded maximum uptake of both primary and secondary nutrients except that K and Mg uptake was maximum at 10 × 2.5 m spacing.